Genetic diversity of Avena landraces accessed by AFLPs - Katsiotis, Andreas; Drossou, Anna; Bladenopoulos, Konstantinos (MTT, 2004)
Cultivated oats, Avena sativa L. and A. byzantina C. Koch, rank fifth among cereals in world production. Most varieties during the 18th, 19th and early 20th centuries were landraces that were heterogeneous mixtures well adapted to the geographical and ecological regions planted (Zeven, 1998). From these landraces a number of modern cultivars have been developed either through the direct selection of single plants or by crosses between the selections. In the present study we try to investigate the genetic relationships among different oat landraces using molecular markers. Three hundred landraces collected from different parts of Europe were screened. DNA was isolated from young leaves of at least 40 seedlings from each landrace. The Amplified Fragment Length Polymorphism (AFLP), a reproducible and reliable molecular marker generating method, was used (Jones et al. 199). A total of 64 different primer pair combinations were tested and the most informative one was chosen. The AFLP reaction products were separated, scored and analysed using an ABI Prism 310 Genetic Analyser. Genetic similarities were calculated using the DICE algorithm and UPGMA was used for clustering. Primer pair EcoRI-ACA/CAC-MseI produced more than 250 polymorphic markers, discriminating the 300 entries. Groups, containing genetically related accessions, were formed according to the geographical and climatic site of landrace origin. Zeven, A.C., 1998 Euphytica 104: 127-139; Jones, C.J. et al. 1998. In: Karp, A. et al. (eds.). Molecular tools for screening biodiversity. London: Chapman & Hall. p. 191-192.
Keywords: Ka; landrace; molecular markers; UPGMA; DICE